Coleman Automorphisms of Some Metabelian Groups - Jingjing Hai; Yanxia Li; Xian Ling (Journal of Mathematics)
In this study, the approach is through the projective limits, and we obtain some characterizations of the Coleman automorphism groups of a split metabelian group and a generalized dicyclic group. An application of our results is a generalization of the result of Z. Li and Y. Li.